Secondary-Level English Teachers’ Perceptions and Experiences of School-based Training for Professional Development - Bhandari, Bhim Lal; Bhandari, Laxman Prasad; Bhusal, Tilak; Tiwari , Eeba Raj (Lumbini Journal of Language and Literature, 2026)
School-based training promotes sustainable development and addresses specific educational needs by offering teachers hands-on, collaborative, and context-specific professional development. However, studies on post-training reflections from participant teachers have been overshadowed. The study aimed to explore English teachers’ perceptions of school-based teacher training and the challenges they face in applying it in classrooms. Using a narrative inquiry method, we conducted in-depth interviews with four secondary-level English language teachers to explore their perceptions and experiences of school-based training. The findings highlight teachers’ positive perceptions of school-based training programs that address the teachers’ pedagogical skills within a particular school context. The study underscores the need for teachers’ professional development and a stronger institutional support to overcome implementation challenges faced in English language classrooms. The findings also emphasize teachers’ preference for real-class pedagogical skills enhancement programs for their professional development. The study’s implications may provide policymakers, administrators, and teacher educators with valuable insights to enhance their understanding of school-based training and improve the overall teaching-learning process in real classroom settings.